Investigation of the effects of high hydrostatic pressure on the functional properties of pea protein isolate. (16th December 2022) - Kalayci, Asuhan; Ozel, Baris; Oztop, Mecit Halil; Alpas, Hami
Abstract: This study investigates the effects of high hydrostatic pressure (HHP) on some functional properties of pea protein isolate (PPI). HHP was combined with various temperature and pH conditions to investigate the combined effects of HHP‐based food processing conditions on the functional properties of PPI. Herein, PPI solutions prepared at different pH conditions (3.0, 5.0, and 7.0) were subjected to 300, 400, and 500 MPa HHP treatment at 25 and 50°C for 5 min. Water‐holding capacity (WHC), solubility, and emulsification activity of PPI samples were determined. Additionally, nuclear magnetic resonance (NMR) relaxometry and Fourier transform infrared spectroscopy experiments were performed for further analysis. Maximum WHC ( p  < 0.05) was observed for the samples treated at 500 MPa‐pH 5.0‐50°C whereas maximum solubility ( p  < 0.05) belonged to the samples subjected to 300 MPa‐pH 7.0‐50°C treatment conditions. Better emulsification activity was achieved at pH 3.0 regardless of the pressure level applied. The novelty of this study is that NMR relaxometry was introduced as a fast/nondestructive technique to investigate the changes in the functional properties of PPI samples and one of the functional parameters was correlated with NMR relaxation data. Herewith, the longest transverse relaxation time ( T 2 ) ( p  < 0.05) belonged to the samples with maximum WHC. The results showed that HHP is able to modify the functional properties of PPI at specific temperature‐pH combinations, and NMR relaxometry technique has a high potential for such studies. Practical Applications: High hydrostatic pressure (HHP) is an emerging technology which is used for its diverse range of applications in food science and technology. Modification of physicochemical and functional properties of food ingredients is one of the latest applications of HHP treatment. This study demonstrated that HHP treatment was able to modify some functional properties of pea protein isolate (PPI) samples such as water‐holding capacity (WHC), solubility, and emulsification activity. In addition to pressure level, pH and temperature were also effective on modifying the functional properties of PPI samples. For instance, a high pressure (500 MPa) was required to improve WHC whereas lower pressures (300 MPa) improved the solubility of the samples at high pH and temperature. The results of this study could be used in model HHP studies to improve some functional properties of PPI for different purposes. Abstract :